2019
DOI: 10.1021/acs.inorgchem.9b02358
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of a Superior Proton Conductor by Confining Tetraethylenepentamine in the Pores of ZIF-8 To Induce Further Adsorption of Water and Carbon Dioxide

Abstract: In this work, we present a new strategy toward the design and preparation of a metal−organic framework-or porous coordination polymer-based superior proton conductor. We chose a robust metal−organic framework, ZIF-8, as the host and a flexible aliphatic alkylpolyamine, tetraethylenepentamine (TEPA), as the guest, and we successfully prepared an encapsulation compound TEPA@ ZIF-8 via the facile insertion of TEPA into the pores of ZIF-8, which was characterized by microanalysis, thermogravimetric analysis, IR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As shown in Figure a and Figure S7, the proton conductivity of 1 significantly improved when increasing the relative humidity between 43 and 99%, with the values varied from 6.06 × 10 –7 S cm –1 at 43% RH to 1.90 × 10 –5 S cm –1 at 75% RH and 4.86 × 10 –5 S cm –1 at 99% RH. This phenomenon of highly humidity-dependent proton conductivity also commonly appeared in water-assisted MOF-based proton conducting materials, implying that the adsorbed water molecules have an important role in constructing the well-defined hydrogen-bonding network that functions as an effective proton-transport pathway in the framework. Furthermore, the water-adsorption/desorption isotherm in Figure b showed the amount of water molecules being adsorbed increased when increasing the relative water-vapor pressure, which further demonstrated that this hybrid material can adsorb more water molecules into the channels under higher relative humidity.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure a and Figure S7, the proton conductivity of 1 significantly improved when increasing the relative humidity between 43 and 99%, with the values varied from 6.06 × 10 –7 S cm –1 at 43% RH to 1.90 × 10 –5 S cm –1 at 75% RH and 4.86 × 10 –5 S cm –1 at 99% RH. This phenomenon of highly humidity-dependent proton conductivity also commonly appeared in water-assisted MOF-based proton conducting materials, implying that the adsorbed water molecules have an important role in constructing the well-defined hydrogen-bonding network that functions as an effective proton-transport pathway in the framework. Furthermore, the water-adsorption/desorption isotherm in Figure b showed the amount of water molecules being adsorbed increased when increasing the relative water-vapor pressure, which further demonstrated that this hybrid material can adsorb more water molecules into the channels under higher relative humidity.…”
Section: Resultsmentioning
confidence: 87%
“…MOF pellets were sealed for 24 h in different humidities and equilibrated for 30 min under each test condition before the AC impedance test. The relative humidity was controlled by different saturated salt solutions, which were solutions of H 2 O (100% RH), Na 2 SO 4 (93% RH), KCI (87% RH), NaCl (75% RH), and NaBr (58% RH). ,, Nafion/MOF composite membranes were cut into circles with a 5 mm diameter. The thickness was measured to be 0.2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Three new proton conduction composites Im@1-3 were successfully obtained by encapsulating imidazole molecules into the pores of 1-3. [36][37][38] The proton conduc-tion behaviors of 1-3 and Im@1-3 were investigated via their alternating current (AC) impedance spectra under different controlled humidities and temperatures. [39][40][41] Amazingly, with the aperture sizes of 1-3 decreased, their proton conductivities increased significantly under the same conditions.…”
Section: Introductionmentioning
confidence: 99%